Importation of Tropical Fruits from Thailand - Edward A. Evans; Sikavas Nalampang (EDIS, 2008)
FE719, an 8-page fact sheet by Edward A. Evans and Sikavas Nalampang, assesses the price competitiveness of imports of longan and lychee, outlines import regulations and highlights Thailand’s production and export trends for these commodities. Includes references. Published by the UF Department of Food and Resource Economics, August 2008.